Philippines : Selected Issues. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2013)
This article is an empirical analysis on tax collections in the Philippines. The tax system is characterized by a rule of tax incentives provided by 13 investment agencies. Tax collections showed regular growth. The GDP ratio increased from 12.1 percent (2009) to 12.8 percent (2012), but the revenue-to-GDP ratio was low to fill large gaps for education, health, and infrastructure; therefore the authorities encompassed the sin taxes (alcohol and tobacco excises). The most important source of income for the Philippines is the labor export. This large-scale labor emigration fetches a sufficient amount of annual inflows of more than 9 percent of GDP.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet